Fast Simulation of the Flow Field in a VAWT Wind Farm Using the Numerical Data Obtained by CFD Analysis for a Single Rotor - Yutaka Hara; Md. Shameem Moral; Aoi Ide; Yoshifumi Jodai (Energies)
The effects of an increase in output power owing to the close arrangement of vertical-axis wind turbines (VAWTs) are well known. With the ultimate goal of determining the optimal layout of a wind farm (WF) for VAWTs, this study proposes a new method for quickly calculating the flow field and power output of a virtual WF consisting of two-dimensional (2-D) miniature VAWT rotors. This new method constructs a flow field in a WF by superposing 2-D velocity numerical data around an isolated single VAWT obtained through a computational fluid dynamics (CFD) analysis. In the calculation process, the VAWTs were gradually increased one by one from the upstream side, and a calculation subroutine, in which the virtual upstream wind speed at each VAWT position was recalculated with the effects of other VAWTs, was repeated three times for each arrangement with a temporal number of VAWTs. This method includes the effects of the velocity gradient, secondary flow, and wake shift as models of turbine-to-turbine interaction. To verify the accuracy of the method, the VAWT rotor power outputs predicted by the proposed method for several types of rotor pairs, four-rotor tandem, and parallel arrangements were compared with the results of previous CFD analyses. This method was applied to four virtual WFs consisting of 16 miniature VAWTs. It was found that a layout consisting of two linear arrays of eight closely spaced VAWTs with wide spacing between the arrays yielded a significantly higher output than the other three layouts. The high-performance layout had fewer rotors in the wakes of the other rotors, and the induced flow speeds generated by the closely spaced VAWTs probably mutually enhanced their output power.